Built environment energy trade-offs scaling. (15th December 2017) - Pan, R.; Gutowski, T.G.; Sekulic, D.P.
Abstract: In this study, a scaling of a series of high level built environment energy models has been introduced, enabling an assessment of energy trade-offs in terms of selected dimensionless governing parameters. The developed models' additional objective is to offer a tool needed to assess the order of magnitude estimates of an influence a system may have on the environment in terms of both the resources utilization and an impact of the built environment's heat dissipation (thermal footprint) on the surroundings. Moreover, the approach enables an assessment of energy trade-offs trends of change caused by the changes in individual contributions of the subsystems. The significance and innovativeness of the models are in an attempt to identify relevant energy trade-off dimensionless parameters. The models are not intended to offer a full scale analysis of energy flows but they can be used at multiple systems' scales. The complexity of the models can be increased based on the adopted set of assumptions. An applicability of the models was demonstrated by the analysis of the three categories of systems: (i) an automobile factory, (ii) a passive house and (iii) a zero energy building. The empirical data sets and their changes illustrate the scaling approach applicability. Highlights: Dimensionless parameters governing energy tradeoffs for built environments are defined. A series of models featuring building systems under different conditions are developed. The models were implemented for various building types. The approach identifies the domains of operating points for each building type.